Aphicidal activity screening of plant extracts from Pistacia lentiscus (Anacardiaceae) - LEBBAL, Salim (ENTOMOLOGIA HELLENICA, 2023)
The excessive use of chemical pesticides has generated many problems to the human health and the environment. To reduce these problems, the use of biopesticides deriving from plants has a lot of advantages. In this context, the aim of this study was to investigate the effect of Pistacia lentiscus L. extracts on insect pests. In vitro tests of five essential oil concentrations (EOs) and five aqueous extracts were performed with respect to their efficacy against the rosy apple aphid Dysaphis plantaginea (Passerini). The obtained results revealed that the concentration of 9% was the most toxic against aphids (mortality rate of 50.77%), while the concentration 5% was the most repellent (repellency percentage -RP- 53.33%) among the examined aqueous extracts. Concerning the EOs, the 10000ppm treatment was the most efficient with a mortality rate of 71.13% and an RP of 66.67%.